2018
DOI: 10.1186/s12879-018-3509-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features and spatial clusters of hand, foot, and mouth disease in Qinghai Province, China, 2009–2015

Abstract: BackgroundHand, Foot, and Mouth Disease (HFMD) is most frequently caused by Enterovirus71 (EV-A71) or Coxsackie virus A16 (CV-A16), infants and young children are at greatest risk. Describing the epidemiology of HFMD can help develop and better target interventions, including the use of pediatric EV-A71 vaccination.MethodsWe obtained data from the national surveillance system for HFMD cases with onset dates from 2009 to 2015. We defined probable cases as patient with skin papular or vesicular rashes on the han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…The age group of HFMD patients was mainly concentrated in the age group under 36 months; the age group from 12 to 24 months accounted for the highest proportion (45.1%). This figure was entirely consistent with the study of Xu L et al (2018) in Qinghai, China. In that study, 67% of children with HFMD were under 36 months of age (Xu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The age group of HFMD patients was mainly concentrated in the age group under 36 months; the age group from 12 to 24 months accounted for the highest proportion (45.1%). This figure was entirely consistent with the study of Xu L et al (2018) in Qinghai, China. In that study, 67% of children with HFMD were under 36 months of age (Xu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…This ratio was in keeping with the previous reports from outbreaks in Taiwan, Singapore, southern Vietnam, and China. Those previous reports showed a male/female ratio ranging from 1.5:1 to 2.5:1 (Chan et al, 2003;Chen et al, 2007;Van Hoang et al, 2019;Xu et al, 2018). The proportion of patients with HFMD living in rural areas (45.7%) was lower than patients living in urban areas (54.3%).…”
Section: Discussionmentioning
confidence: 66%
“…Although EV71 and CA16 were the most common etiological pathogens in many HFMD cases around the world [37,38], our study showed that other EV was the major pathogens of HFMD in Qingdao during 2013-2018 except 2017. Notably, some other studies showed that other EV, such as CA6 and CA10, was going to become the important causative agents for HFMD in China, Finland, France, and Japan [39][40][41].…”
Section: Plos Onementioning
confidence: 56%
“…It was worth noting that there were many "villages within cities" in urban-rural fringe areas with large number of migrant workers, backward municipal facilities, weak health awareness and poor health environment in China. Some studies indicated that many migrant workers lived with their children, most of whom were under 5 years old and not at school, which leaded to high incidence of HFMD in urban-rural fringe areas [38]. Moreover, the space-time scanning results indicated that the tendency of HFMD in Qingdao City spreaded from urban area to rural area.…”
Section: Plos Onementioning
confidence: 99%
“…Hand, foot, and mouth disease (HFMD), a common childhood infectious disease, is mostly caused by Enterovirus 71 (EV-A71) or Coxsackievirus A16 (CV-A16) and frequently occurs in East and Southeast Asia including China. [ 1 ] HFMD poses a significant threat to public health and was classified as a C-class notifiable communicable disease in China in 2008. The main patient groups susceptible to HFMD are infants and children under 5 years of age.…”
Section: Introductionmentioning
confidence: 99%